Antibacterial activity of AgNPs–TiO2 nanotubes: influence of different nanoparticle stabilizers. Issue 72 (17th December 2020) - Bilek, Ondrej; Fialova, Tatiana; Otahal, Alexandr; Adam, Vojtech; Smerkova, Kristyna; Fohlerova, Zdenka
Abstract : Synergictic antibacterial effect of AgNPs–TiO2 nanotubes is influenced by different nanoparticle stabilizers. Abstract : Enhanced antibacterial properties of nanomaterials such as TiO2 nanotubes (TNTs) and silver nanoparticles (AgNPs) have attracted much attention in biomedicine and industry. The antibacterial properties of nanoparticles depend, among others, on the functionalization layer of the nanoparticles. However, the more complex information about the influence of different functionalization layers on antibacterial properties of nanoparticle decorated surfaces is still missing. Here we show the array of ∼50 nm diameter TNTs decorated with ∼50 nm AgNPs having different functionalization layers such as polyvinylpyrrolidone, branched polyethyleneimine, citrate, lipoic acid, and polyethylene glycol. To assess the antibacterial properties, the viability of Gram-positive ( Staphylococcus aureus ) and Gram-negative bacteria ( Escherichia coli and Pseudomonas aeruginosa ) has been assessed. Our results showed that the functional layer of nanoparticles plays an important role in antibacterial properties and the synergistic effect such nanoparticles and TiO2 nanotubes have had different effects on adhesion and viability of G − and G + bacteria. These findings could help researchers to optimally design any surfaces to be used as an antibacterial including the implantable titanium biomaterials.